Design and application of multiple model predictive control in stroke control of hydrostatic transmission - Ulker, Hakan (Sage Publications Ltd, 2025)
The stroke control of a hydrostatic transmission (HST) has an important role for heavy-duty, on-highway, and off-road vehicles like agricultural and construction equipments along with mining and forestry vehicles to increase energy efficiency and power variability. The author proposes a multiple Model Predictive Controller (MPC) and multiple Model Reference Adaptive Control (MRAC) as a new control strategy for stroke control of HST, and compare their performances. The proposed controllers are based on a linear HST system mathematical model to track complex stroke reference trajectories of primary and secondary regulations under the realistic disturbances such as engine and load torques as a result of type of soil and field road conditions. The results of the Processor in the Loop simulations are encouraging in terms of the MPC having advantages over the MRAC and classical control strategies like being able to be designed for multi-input-multi-output systems, insensitive to external stochastic disturbances such as white noise as well as modeling errors and uncertainties to be implemented on an HST for real-time implementation.
Keywords: heavy-duty vehicles; hydrostatic transmission stroke control; multiple model predictive control; primary and secondary regulation; disturbance rejection